Enhancing Student Resilience through Anti-Bullying Policies: A Qualitative Study - Rofiki, Moh.; Baharun, Hasan; Badriyati, Linda (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
The study aims to identify how anti-bullying policies can build student resilience in dealing with bullying. This resilience functions as a fortress that protects students from the impact of the mistreatment they receive. This research method uses a qualitative approach. This qualitative approach was chosen to obtain broad and in-depth information about building student resilience through anti-bullying risk management—a qualitative approach with a phenomenological type is used to examine subjects such as behavior, motivation, and actions. The study results indicate that student resilience can be built through anti-bullying risk management by identifying bullying risks and receiving support from caregivers, counselors, and teacher support so that students can build resilience well. The implications of this study indicate that by placing bullying risks early on and providing support from caregivers, counselors, and teacher support, students can obtain better emotional protection and build mental strength to face difficult situations. Another aspect is that Islamic boarding schools need to establish a secure, encouraging, and supportive setting for students' growth.